Comparison of Antibacterial Effects of Three Different Methods on Enterococcus Faecalis in the Root Canal System: An in vitro study - Masoud Yousefi; Seyyed Ali Fattahi; soheila darmiani (Mashhad University of Medical Sciences, 2021)
Introduction: Effective cleaning of the canal is one of the most important biological goals of root canal treatment. Enterococcus faecalis is one of the most resistant bacteria following root canal treatment. The aim of this study was to compare the effect of EndoActivator and XP‐Endo Finisher File to the usual method in the cleaning of the infected canals with Enterococcus faecalis. Materials and Methods: The present study was carried out on a total of 56 teeth. In order to induce infection, Enterococcus faecalis was cultured and incubated. The teeth were divided into four groups (with 14 teeth in each group). The XP‐Endo Finisher File, EndoActivator, 5.25% sodium hypochlorite, and normal saline were used in the first, second, third, and fourth groups, respectively. Finally, the number of grown colonies was counted and reported in the CFU/ml unit. Results: The mean number of colonies before using XP-Endo Finisher, EndoActivator, sodium hypochlorite, and normal saline were 169.7×104, 156.5×104, 193.2×104, and 215.9×104 CFU/ml, respectively, with no significant difference. After using XP-Endo Finisher, EndoAvactivator, sodium hypochlorite, and normal saline, the mean number of colonies were reported as 0.71×104, 4.78×104, 0.14×104, and 123.7×104 CFU/ml, respectively, indicating the clearance rates of 99.7%, 96.2%, 99.9%, and 42.9%, respectively. After the intervention, the studied groups were significantly different (p < /em><0.001) in terms of the contamination. The number of colonies in the XP-Endo Finisher group was significantly (p < /em>=0.04) lower than that of the EndoAvactivator group. These values were significantly (p < /em><0.001) lower in the three groups of EndoActivators, XP-Endo Finisher, and sodium hypochlorite than that of the normal saline group. There was no significant difference between the two groups of XP-Endo Finisher and sodium hypochlorite (p < /em>=0.608) and two groups of EndoActivator and sodium hypochlorite (p < /em>=0.507). The use of XP‐Endo Finisher, EndoActivator, and sodium hypochlorite resulted in significantly higher clearance than that reported for normal saline. Conclusion: The highest rates of Enterococcus faecalis clearance were observed in the application of sodium hypochlorite, XP-Endo Finisher, and EndoActivator, respectively.